2013
DOI: 10.1002/smj.2044
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the Gordian knot: The effect of knowledge complexity on employee mobility and entrepreneurship

Abstract: Employee entrepreneurship and employee moves to rival firms (employee mobility) have both been recognized as critical drivers of the transfer of knowledge. Drawing on a unique database of intra‐industry inventor entrepreneurship and mobility events in the U.S. semiconductor industry, I examine the effect of the complexity of inventors' prior patenting activities on their decisions to join a rival firm or found a start‐up. The findings show that even though complexity inhibits knowledge diffusion to rival firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
140
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 77 publications
(233 reference statements)
6
140
1
3
Order By: Relevance
“…Regarding the measures of human capital, X it , previous research using patents to track mobility (detailed in Table ) concluded that inventor mobility is negatively related to productivity, as measured by the number of patent applications per year (Hoisl, ); increases in inventor impact, as measured by average standardized citations (Palomeras and Melero, ); decreases in the complexity of inventions (Ganco, ); decreases in complementarity with others, as measured by the number of co‐inventors (Palomeras and Melero, ); and is higher among inventors residing in Silicon Valley (Cheyre et al , ).…”
Section: Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the measures of human capital, X it , previous research using patents to track mobility (detailed in Table ) concluded that inventor mobility is negatively related to productivity, as measured by the number of patent applications per year (Hoisl, ); increases in inventor impact, as measured by average standardized citations (Palomeras and Melero, ); decreases in the complexity of inventions (Ganco, ); decreases in complementarity with others, as measured by the number of co‐inventors (Palomeras and Melero, ); and is higher among inventors residing in Silicon Valley (Cheyre et al , ).…”
Section: Mobilitymentioning
confidence: 99%
“…Using patents and LinkedIn profiles, we investigate how the mobility of engineers and scientists depends on their human capital. Previous patent‐based research found that mobility increases in inventor productivity, as measured by patent rate (Hoisl, ), inventor impact, as measured by citations (Palomeras and Melero, ), decreases in inventor complexity (Ganco, ), and decreases in complementarity with others, as measured by the number of co‐inventors (Palomeras and Melero, ), while mobility is higher among inventors resident in Silicon Valley (Cheyre, Klepper, and Veloso, ).…”
Section: Introductionmentioning
confidence: 99%
“…Авторы вывели соответствующие факторы для стартапов, выделив три возможных направления по индустриям: (1) собственность со-трудников (employee entrepreneurship) -производство и маркетинг целевой продукции и услуг; (2) собственность академиков (academic entrepreneurship) -процесс научного открытия в академических ин-ститутах; (3) собственность пользователей (user entrepreneurship) -ис-пользование этих продуктов и услуг. Помимо этого было выявлено наличие собственности сотрудников в отраслях, связанных с интел-лектуальной собственностью, с патентами, -в медицине и биотех-нологиях [Ganco, 2013]. Авторы отмечают, что фирмы, созданные предпринимателями, входят на рынок в период роста и зрелости отрасли и скорее соревнуются с уже существующими фирмами, не-жели с ними сотрудничают.…”
Section: собственность основателей бизнесаunclassified
“…При этом наибольшее количество женщин в составе директоров на-блюдается в секторах розничной и оптовой торговли, потребитель-ских товаров, медиа и сферы развлечений; наименьшее -в секторе промышленности, высоких технологий, нефти и газа. Существует различие и на уровне размера компании: в 15% фирм из индекса S&P MidCap400 и 12% из S&P SmallCap 600 в совете присутствуют женщины 20 . На основе опроса 400 компаний выявлено, что жен-щины в совете директоров заставляют топ-менеджмент компании в большей степени фокусироваться на вопросах корпоративного управления, корпоративной ответственности, качественного раз-вития и расширения кругозора, что и требуется в данный момент инвесторам 21 .…”
Section: процесс принятия решений внутри компании: женщиныunclassified
See 1 more Smart Citation